2018
DOI: 10.1002/jcb.27738
|View full text |Cite
|
Sign up to set email alerts
|

Oleuropein induces apoptosis via abrogating NF‐κB activation cascade in estrogen receptor–negative breast cancer cells

Abstract: Oleuropein is one of the most abundant phenolic compounds found in olives.Epidemiological studies have indicated that an increasing intake of olive oil can significantly reduce the risk of breast cancer. However, the potential effect(s) of oleuropein on estrogen receptor (ER)-negative breast cancer is not fully understood.This study aims to understand the anticancer effects and underlying mechanism (s) of oleuropein on ER-negative breast cancer cells in vitro. The effect of oleuropein on the viability of breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 84 publications
2
72
0
2
Order By: Relevance
“…Elamin et al [136] was able to extend the use of Ole to the less responsive basal-like breast cancer cells (MDA-MB-231 cells), and demonstrated its ability to abrogate NF-kB expression, a well-known transcription factor involved in the control of many genes driving cancer development and progression, e.g., inflammation, immune reaction, proliferation, and apoptosis. This last finding was also confirmed by Liu et al [137].…”
Section: Pro-apoptotic and Anti-proliferative Effects Of Oleuropeinsupporting
confidence: 82%
“…Elamin et al [136] was able to extend the use of Ole to the less responsive basal-like breast cancer cells (MDA-MB-231 cells), and demonstrated its ability to abrogate NF-kB expression, a well-known transcription factor involved in the control of many genes driving cancer development and progression, e.g., inflammation, immune reaction, proliferation, and apoptosis. This last finding was also confirmed by Liu et al [137].…”
Section: Pro-apoptotic and Anti-proliferative Effects Of Oleuropeinsupporting
confidence: 82%
“…It provided a comprehensive insight to explain the different response of MCF-7 and MDA-MB-231 cells to the β-estradiol stimulation. Meanwhile, given the MDA-MB-231 is triple negative breast cancer cell without oestrogen receptors [47,48], the results also confirmed that the membrane phase and lipid diffusion were not affected by β-estradiol in MDA-MB-231 cells, indicating that the slow subdiffusion of CT-B could be used to assess the response of lipid raft-related receptors in specific pathophysiological processes. And the increased area of Lo phase was near to that of laser focal volume, resulting in the increased proportion of slow subdiffusion.…”
Section: Discussionmentioning
confidence: 67%
“…The slow subdiffusion component (ie, t > 100 ms, D < 0.2 μm 2 s −1 ) remained undetected. The underlying reason for this difference compared with MCF-7 cells was that MDA-MB-231 cells were triple negative breast cancer cells without oestrogen receptors, which resulted in less response to the stimulation of β-estradiol [47,48]. The histogram of CT-B diffusion time showed that the diffusion time was significantly increased above 100 ms, and the related diffusion (Figure 5B,F).…”
Section: The Effect Of β-Estradiol On the Membrane Rafts In Mcf-7 Cmentioning
confidence: 99%
“…TIPE2 is found to be involved in the positive regulation of tobacco-promoted lung carcinogenesis by modulating the expression of NF-κB and NF-κB-regulated gene products, such as Cox-2, survivin, Cyclin D1, MMP-9, and CXCR-4. NF-κB is a transcription factor that regulates the expression of genes involved in lung carcinogenesis [73][74][75][76][77][78][79][80][81][82][83]. Alvira and their group reported high levels of nuclear NF-κB in lung cancer tissues and enhanced NF-κB activity well-correlated with more advanced disease in lung adenocarcinoma [84].…”
Section: Discussionmentioning
confidence: 99%